Enzyme activity of the tilapia (Oreochromis niloticus) antioxidant defense system as a model of exposure to the titanium dioxide (TiO2) nanoparticle (Research, Society and Development, 2021)
The biochemical biomarkers of fish can be useful tools in the investigation of the presence of nanoparticles (NPs) in the aquatic system. However, it is extremely important to know the responses of these biomarkers to exposure to this xenobiotic in order to try to establish a model for biological monitoring. Thus, our objective was to determine the response of the enzymes catalase (CAT) and glutathione S-transferase (GST) of tilapia (Oreochromis niloticus) after 48 and 96 hours of exposure to a titanium dioxide nanoparticle (NP-TiO2). For this purpose, 10 fish were exposed to: 0 (control), 1, 5, 10 and 50 mg.L-1 of NP-TiO2. Then, the liver was used to determine the biomarkers. We did not observe a significant variation in CAT in tilapia exposed for 48h to PN. However, after 96 h the CAT was higher in the exposed animals at the highest tested concentrations (10 and 50 mg.L-1). Even at these concentrations, the activity was higher in the animals exposed for 96 hours. For GST, in the first 48 h the activity was lower in animals exposed to 1, 5 and 50 mg.L-1 of TiO2, whereas, in the exposure of 96 h, greater activity of GST was observed in animals exposed to 50 mg.L-1. Comparing the exposure time, in all concentrations tested, the hepatic GST activity was higher in the animals exposed for 96 h. Thus, in addition to the concentration, the time of exposure to NP seems to influence the response of the enzymes, increasing their activity.